The Effect of K3 Culture on Work Accidents of Tofu Industrial Workes in Tinalan Kediri - Wahyu Purnomo Jati; Rofik Damayanti; Endra Widiyanto; Agustin Widyowati (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2025)
Work accidents in the industrial sector, particularly in the TOU industry in Tinalan, Kediri, remain a critical issue affecting worker safety and productivity. This study aims to examine the influence of Occupational Health and Safety (K3) culture on the incidence of workplace accidents among TOU industrial workers. The research employs a quantitative approach with a cross-sectional survey method, involving (mention number of respondents) respondents from various departments within the TOU industry. Data were collected through structured questionnaires, workplace observations, and interviews with safety officers.The findings indicate that a strong K3 culture, characterized by routine safety training, compliance with safety protocols, and proper use of personal protective equipment (PPE), significantly reduces the frequency and severity of work accidents. Statistical analysis using (mention statistical method, e.g., regression analysis, correlation test) shows a (mention percentage or significance level, e.g., p < 0.05) correlation between the level of K3 culture implementation and the occurrence of workplace accidents. Workers in environments with high adherence to K3 standards reported (mention percentage reduction in accidents, if available) fewer accidents compared to those with lower compliance levels.The study concludes that strengthening the implementation of K3 culture through enhanced safety policies, continuous monitoring, and increased worker awareness is essential in minimizing work-related injuries and improving overall workplace safety. It is recommended that TOU industries in Tinalan, Kediri, adopt a more proactive approach to safety management to ensure a safer working environment.